IMPLEMENTATION OF MODEL VIEW CONTROLLER (MVC) ARCHITECTURE ON BUILDING WEB-BASED INFORMATION SYSTEM - Shofwatul 'Uyun; Muhammad Rifqi Ma'arif (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2010)
The purpose of this paper is to introduce the use of MVC architecture in web-based information systemsdevelopment. MVC (Model-View-Controller) architecture is a way to decompose the application into threeparts: model, view and controller. Originally applied to the graphical user interaction model of input,processing and output. Expected to use the MVC architecture, applications can be built maintenance of moremodular, rusable, and easy and migrate. We have developed a management system of school fees at the highschool. The developed system uses the MVC (Model-View-Controller Architecture) to provide a description ofhow the MVC works and its benefits.Keywords: web-based information system, MVC, modularity, reusability.